2014
DOI: 10.1590/s1516-89132014000100001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizobacteria from field grown Genetically Modified (GM) and non-GM maizes

Abstract: This study was done to examine the rhizobacteria from field grown Genetically Modified (GM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
8
8
0
Order By: Relevance
“…Clinical isolates of these control strains were tested in the same setup as P. aeruginosa , but no HCN could be detected. The findings were in accordance with Bumunang & Babalola32.…”
Section: Resultssupporting
confidence: 90%
“…Clinical isolates of these control strains were tested in the same setup as P. aeruginosa , but no HCN could be detected. The findings were in accordance with Bumunang & Babalola32.…”
Section: Resultssupporting
confidence: 90%
“…Manuscript to be reviewed PGPR produce catalase enzyme (Mumtaz et al, 2017) that helps plants to withstand under stressed conditions by neutralizing the effect of hydrogen peroxide. In present study, all tested isolates were catalase positive, which is correlated with previous work as described by Chaiharn et al (2008) and Bumunang and Babalola (2014). Similarly, Shruti et al 2013 2011observed that out of ten strains, only five were urease positive.…”
Section: Discussionsupporting
confidence: 92%
“…Out of 20 isolates, seven isolates gave positive results for phosphate solubilization. These findings are in accordance with the results of Bumunang and Babalola (2014). Similarly, Hussain et al (2013) found 32 bacterial isolates with phosphorus solubilizing activity.…”
Section: Discussionsupporting
confidence: 89%
“…Genus Sphingomonas discovered and presented the physiology and ecology by White et al [43] and Ali et al [44] reported genus Sphingomonas has a ability of nitrogen fixation, phosphate and potassium solubilization and Sphingomonas together with Burkholderia, Bacillus, Pseudomonas have been used biofertilizing microbes. Recently Bumunang and Babalota [45] examined the rhizobacteria from field grown GM maize in South Africa as follows species of Pseudomonas, Aeromonas, Sphingomonas, Burkholderia, Bacillus, Stenotrophomonas, Achromobacter, Ewingella, they have catalase activity, ammonia production, IAA production, phosphate solubilisation and antifungal activity. Our results also found the rhizospheric bacteria in acrisols and ferrasols with species of bacilli, betaproteobacteria as Burkholderia, Acidobacteria and Sphingomonas.…”
Section: Resultsmentioning
confidence: 99%